Altruism, Fertility, and the Value of Children: Health Policy Evaluation and Intergenerational Welfare - Javier A. Birchenall; Rodrigo R. Soares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2007)
This paper accounts for the value of children and future generations in the evaluation of health policies. This is achieved through the incorporation of altruism and fertility in a “value of life” type of framework. We are able to express adults' willingness to pay for changes in child mortality and also to incorporate the welfare of future generations in the evaluation of current policies. Our model clarifies a series of puzzles from the literature on the “value of life” and on intergenerational welfare comparisons. We show that, by incorporating altruism and fertility into the analysis, the estimated welfare gain from recent reductions in mortality in the U.S. easily doubles.
Keywords: 330; value of life; mortality; fertility; altruism; intergenerational welfare; willingness to pay; Gesundheitspolitik; Wert des Menschenlebens; Kinder; Bewertung; Altruismus; Fertilität; Generationengerechtigkeit; Zahlungsbereitschaftsanalyse; Theorie